Dental amalgam and antibiotic- and/or mercury-resistant bacteria - Roberts, M. C. (2018)
Mercury emitted from dental amalgam may select for increased numbers of antibiotic- or mercuryresistant commensal bacteria in patients and increase their risk for bacterial diseases that are resistant to common therapies. We hypothesized that the presence of dental amalgams would increase the level of mercury-, tetracycline-, ampicillin-, erythromycin-, or chloramphenicolresistant oral and urinary bacteria as compared with levels in children receiving composite fillings. Samples were collected at baseline, 3-6 months after the initial dental treatment, and annually for 7 years of follow-up. There were no statistically significant differences between treatment groups in the numbers of bacteria growing on antibiotic- or mercury-supplemented plates. This study provided no evidence that amalgam fillings on posterior teeth influenced the level of antibiotic- or mercury-resistant oral or urinary bacteria as detected by culture.